1987
DOI: 10.1212/wnl.37.7.1165
|View full text |Cite
|
Sign up to set email alerts
|

Acquired aphasia in childhood

Abstract: We studied eight children with acquired aphasia. All had left hemisphere lesions. In most, the correlation between the CT lesion site and the resulting aphasic syndrome duplicated an anatomic-clinical correlation described in adults. Rapid recovery of language fluency distinguished the children from reported adults. Late follow-up indicated poor scholastic achievements, reflecting an acquired handicap in new learning. Anatomic-clinical correlates and recovery patterns suggest that brain organization for langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 0 publications
3
22
0
Order By: Relevance
“…These authors argued that the two hemispheres have the same cognitive potential at birth, and that lateral specialization develops gradually during childhood. Cranberg and coworkers (Cranberg et al 1987) studied acquired aphasia in eight children with a mean age of 10 years. The present study corroborates their finding of a good recovery from aphasia and a presence of general learning problems.…”
Section: Cognitive Functioning At Follow-upmentioning
confidence: 99%
“…These authors argued that the two hemispheres have the same cognitive potential at birth, and that lateral specialization develops gradually during childhood. Cranberg and coworkers (Cranberg et al 1987) studied acquired aphasia in eight children with a mean age of 10 years. The present study corroborates their finding of a good recovery from aphasia and a presence of general learning problems.…”
Section: Cognitive Functioning At Follow-upmentioning
confidence: 99%
“…In children, it has been reported that the plasticity of the brain is greater than in adults and the outcome of acquired aphasia is thought to be better in children (Cranberg et al, 1987;Loonen & van Dongen, 1990;Martins & Ferro, 1991;Satz & Bullard-Bates, 1981). The immature brain of a child has more strategies and capacity for recovery than the adult brain, and children have the potential to transfer language to either the right hemisphere or to functionally related (but uncommitted) areas of the left hemisphere, with such differences from adults are thought to be part of the explanation for the good prognosis of acquired childhood aphasia (Martins & Ferro, 1992).…”
Section: Evidence From Childhood Aphasia -Functional Reorganizationmentioning
confidence: 99%
“…It has been recognized that the prognosis of acquired aphasia is better in children than in adults, and with children showing recovery that is faster and more complete (Cranberg, Filley, Hart, & Alexander, 1987;Lenneberg, 1967;Satz & Bullard-Bates, 1981). The main factors that are considered to influence the prognosis of childhood aphasia are the age at onset, cause, severity and bilaterality of lesions, and type of aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a series of 32 children with mostly left hemisphere lesions reported by Alajouanine and Lhermitte (1965) disturbed reading performance was reported in 18 (56.25%) of the children. Persistent reading difficulties were also documented in 5 of the 8 children (62.5%) with left hemisphere lesions reported by Cranberg, Filley, Hart, and Alexander (1987). Reading difficulties have been reported, by some, to be short-lived, being most common in the acute stages postonset, but often making a rapid and complete recovery (e.g., Hecaen, 1983;Dennis, 1980).…”
Section: Introductionmentioning
confidence: 97%